How Does Profitability Moderate the Impact of Financial Performance on Firm Value? - Adhi Widyakto; Oktavie Fresiliasari; Ayu Nurafni Octavia; Masudul Alam Choudury; Rosylin Mohd Yusof (KEUNIS, 2026)
This study investigates the impacts of financial performance—assessed through blockholding, board size, and capital structure (debt-to-equity ratio/DER) variables—on firm value, with profitability (ROA) acting as a moderating variable. Data obtained from a sample of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2020 to 2023 were analyzed using panel data regression analysis in EViews 13. The findings reveal that blockholding exerts a negative and significant influence on firm value, indicating that ownership concentration may lead to agency conflicts and weaken investor confidence. Conversely, DER shows a positive and significant relationship with firm value, suggesting that a sound capital structure can enhance firm performance and signal financial stability to the market. Meanwhile, board size does not have a significant effect on firm value, implying that governance quality is more vital than the number of directors. Furthermore, profitability (ROA) does not moderate the relationship between blockholding, board size, or DER and firm value. These results emphasize that ownership and capital structures remain the key determinants of firm value, and profitability alone cannot strengthen these relationships. This study has practical implications for management and investors seeking to increase firm value through effective governance and optimal capital structure management.